UPAYA PENDAMPINGAN PEMASARAN PRODUK MELALUI PERBAIKAN KEMASAN, LABEL, DAN PENGURUSAN IZIN SPP-IRT UD. SAMUDERA MIRJA DI GAMPONG UJUNG KALAK - Sarita Ayu; Muhammad Agam Thahir; Dini Marliana; T Hamdan; Sariana Sariana; Syahrul Muharram; Muhammad Fadli; Dimas Kusmayadi (Universitas Teuku Umar, 2022)
Ocean mirja trading business is located in Ujung Kalak village, West Aceh district. UD is engaged in the processing of fishery products, one of which is processed keumamah fish. Keumamah fish is a traditional Acehnese cuisine made from tuna and skipjack fish raw materials, keumamah fish are often also called wooden fish because of their hard texture like wood. A business, whether high, medium or small, is established with the aim of making a profit. To get big profits, a product marketing is needed. Indicators that must be considered in product marketing include packaging, product name and SPP-IRT permit. Packaging is one element of the product strategy used to attract the attention of consumers to buy the product. Small entrepreneurs usually pay less attention to packaging, product names and licensing so that the products they sell are less attractive. Here packaging improvements are used in helping partner entrepreneurs to increase sales of the products they produce. After making improvements to the packaging and processing the SPP-IRT permit on the product, it can increase the selling price which is slightly higher. The improvement process in this mentoring effort has several stages, namely, interviews and observations, consultations and discussions, practice, and finally the product marketing trial process. After the process of mentoring efforts to improve packaging that has been carried out, namely designing packaging, replacing pouch packaging with plastic bottles. Mentoring activities for 4 months were carried out well and partners were directly involved as determinants and implementers of activities so that there was no reluctance from partners to implement new packaging and follow the process of issuing SPP-IRT.